The early Humiliati - Andrews, Frances 19XX- (Cambridge studies in medieval life and thought, 1999)
This book is the first major study in English of a group of late twelfth-century religious enthusiasts, the early Humiliati, who were condemned by the Church as heretics in 1184. However, in a remarkable transition, they were reconciled seventeen years later and went on to establish a highly successful religious order in north Italy. The Humiliati have been accorded little attention in previous studies both because of their local nature and because of the suppression of the Order in 1571, after one of their number made a disastrous attempt to murder Charles Borromeo. Using a combination of a wide range of sources, the nature of the early movement and its processes of institutional development are reconstructed. The book also includes a Bullarium Humiliatorum, a calendar of papal and episcopal letters and privileges, which will be of great use to scholars in the field.